Interactive functional anatomy - Hillman, Susan K., 1952 (London : Primal Pictures, 2006)
Contains a complete 3-D model of the entire skeleton with muscles, ligaments, bones, arteries, and nerves, complete with detailed text describing each body part and its function
Title from container
System requirements for PC: Pentium processor; at least 64 MB RAM; display size 800x600 or greater and more than 256 colors; Windows 95, 98, 2000 or NT 4.0; DVD-ROM drive
System requirements for Macintosh: PowerMac; at least 64 MB RAM; display size 800 x 600 or greater and more than 256 colors; Mac OS 8.6 or later; DVD-ROM drive
Keywords: Anatomy; Human anatomy